Analisis efektivitas penggunaan excavator berbasis hours meter menggunakan metode OEE dan Six Big Losses di PT. Uniteda Arkato Site Banyuwangi - Aditya, Dewi Mardiana; Syaifullah, Hafid (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT. Uniteda Arkato is a company that operates in the heavy equipment and contractor rental sector. The problem of suboptimal unit performance occurred in one of the company's excavators, the Komatsu PC 300 Bucket Excavator. This research aims to determine the effectiveness of using excavators and minimize losses. The methods used are Overall Equipment Effectiveness (OEE) and Six Big Losses. The research results show that the OEE value is still below standard, 77% with an Availability value of 88%, Performance Efficiency of 93%, and Quality of 94%. Furthermore, based on the Six Big Losses analysis, the biggest loss occurred due to the Reduce Speed ??Losses factor, 34% caused by large downtime. Improvement recommendations are proposed to increase unit effectiveness, such as establishing a maintenance schedule, checking and replacing components, and operator training. It is hoped that this research can contribute to increasing the effectiveness of unit use and company productivity.